[Fabrication of parts at Brechin Castle, Trinidad] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Fabrication of parts for the frond end loader at the Transport and Field Engineering Department, Brechin Castle.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago; Agricultural machinery -- Parts - Trinidad and Tobago; Caroni (1975) Limited